Determination of the lead environment in samarium – Lead oxide-borate glasses and vitroceramics using XANES and EXAFS studies. (September 2020) - Dehelean, A.; Rada, S.; Zhang, J.
Abstract: In this study, the structural and spectroscopic properties of a serie samarium doped lead oxide - borate glasses and vitroceramics in the xSm2 O3 ·(100-x)[4B2 O3 ·PbO] composition where x = 0, 10, 20, 40 mol % Sm2 O3 were reported. The samples were prepared by the conventional melt-quenching method and were characterized by the analysis of X-Ray diffraction and the investigations of Raman, FTIR, UV–Vis, PL, EPR and XAS spectroscopies. The XRD patterns reveal amorphous nature of the samples with lower Sm2 O3 content up to x = 20 mol%. For the sample with x = 40 mol% Sm2 O3, the analysis of XRD data indicates the presence of two Sm(BO2 )3 crystalline phases with monoclinic structure and PbO crystalline phase with orthorhombic and tetragonal structure. FTIR and Raman spectra indicate that the evolution of [BO3 ] and [BO4 ] structural units were modified by increasing of Sm2 O3 content up to 40 mol % in the host matrix. UV–Vis data show: i) the stronger transitions due to the presence of PbO bonds from [PbO3 ] structural units, for samples with lower Sm2 O3 content; ii) the conversion of the [PbO3 ] structural units in [PbO4 ] structural units for the sample with higher Sm2 O3 content (x = 40 mol %). The optical band gap values are between 4.03 and 4.32 eV for the direct transitions and between 3.94 and 4.15 eV for the indirect transitions. PL data show the emission bands corresponding to the f-f electronic transitions of Sm 3+ ions. The intensity of the emission increases as the concentration of the Sm +3 ions increases up to 10 mol% and after this it decreases. This decrease in PL intensity is due to the energy transfer from excited Sm +3 ions into non-excited Sm +3 ions or cross relaxations because the distance between samarium ions were decreased by the doping after 10 mol % Sm2 O3 and the exchange and inter-ionic interactions were also enhanced. The analysis of EPR data shows two broad signals centered at g~9.7 and g~2.11, which can be due to the isolated Sm 3+ ions and Sm 3+ -Sm 3+ pair centers. A detailed study of XANEX and EXAFS data was used to evaluate the environment of the lead atoms, coordination number and interatomic Pb–O distance in the studied glasses and vitroceramics. In the glasses can be estimated the presence a greater number of longer Pb–O distances while in vitroceramic exists smaller Pb–O distances and a better packing arrangement. Highlights: The formation of Sm(BO2 )3 crystalline phases crystalline phase at higher dopant levels. The f-f electronic transitions of Sm 3+ ions. Two broad EPR signals centered at g~9.7 and g~2.11 corresponding to the isolated Sm 3+ ions and Sm 3+ -Sm 3+ pair centers. The highly distorted [PbOn ] geometry (n = 4 and 6) and non-equivalent Pb–O distances ·. Massicot and litharge PbO crystalline phases.